Evaluating the policy of removal and resettlement for residents of unsafe slums in greater Cairo according to the principles of sustainable development: Case study of Asmarat neighborhood - Hassan, Mohamed Sobhi AbdelGhani; Ibrahim, Mohamed AbdelBaqy; Hassan, Ghada Farouk; Khalifa, Marwa AboulFotouh (Journal of engineering sciences and information technology, 2023)
Policies for developing slums in developing countries have diversified to confront the slums crisis. The strategy of removal and resettlement comes as one of these policies. Although its advantages in providing housing units with higher quality, more stable ownership, and exploiting the evacuation areas in development projects, there are many experiences that indicate that it leads to serious risks, which the most important of them is the destruction of the social and economic structure of local society in slums. The research problem is that although governments consider resettlement is a healthy strategy, its adoption may harm the population, as moving them leads to destruct the social and economic structure, unless following the principles of sustainable urban development. The research paper aims to study the development of slums in the period after the Egyptian revolution in 2011, which is considered the beginning for appearing of new development partners, by studying, analyzing and evaluating one of the newest projects, which called Asmarat neighborhood in Mokattam, Egypt, and comparing results with the dimensions of sustainable urban development, by collecting information , personal interviews of officials and residents, field visits, analyzing this data and deducing the extent to which the dimensions of sustainable urban development have been achieved. The research concluded that the percentage achieved is 66%, and that the project concerned mainly the urban dimension. Hence, the research recommends the need to establish the rules of community participation, move from theory to practice with using modern urban strategies such as resilience housing approaches, implement experimental projects, and follow them in developing strategies for providing housing, particularly in unsafe areas and generally for low-income housing.